2016
DOI: 10.1097/qai.0000000000001144
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Marginal Cost of Male Circumcision in Rural Rakai Uganda

Abstract: Male circumcision (MC) is an effective intervention to reduce HIV acquisition in men in Africa. We conducted a cost analysis using longitudinal data on expenditures on services and community mobilization to estimate the marginal cost of MC over time and understand cost drivers during scale up. We used a time-series with monthly records from 2008 to 2013, for a total of 72 monthly observations, from the Rakai MC program in Uganda. GLM models were used to estimate the marginal cost of a MC procedure. The margina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Eleven studies presented cost data [14,25,[36][37][38][39][40][41][42][43][44], three of which were related to articles included in the main effectiveness review. Studies were published between 2012 and 2018 and took place in Kenya [38,41], South Africa [39,42,43], Tanzania [44], Uganda [36,37,40], and Zimbabwe [14,25]. Descriptions of included cost studies and their outcomes are presented in Table 5.…”
Section: Costsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven studies presented cost data [14,25,[36][37][38][39][40][41][42][43][44], three of which were related to articles included in the main effectiveness review. Studies were published between 2012 and 2018 and took place in Kenya [38,41], South Africa [39,42,43], Tanzania [44], Uganda [36,37,40], and Zimbabwe [14,25]. Descriptions of included cost studies and their outcomes are presented in Table 5.…”
Section: Costsmentioning
confidence: 99%
“…Descriptions of included cost studies and their outcomes are presented in Table 5. Seven of the included studies assessed community-based interventions [14,36,[40][41][42][43][44], two assessed school-based interventions [25,39], and two assessed facility-based interventions [37,38]. Generally, cost studies showed that service delivery interventions may create economies of scale and efficiencies when implemented widely.…”
Section: Costsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 9 ] Task shifting of VMMC has been successful in other African countries[ 10 – 12 ] and has reduced costs. [ 13 , 14 ] In particular, CAs should contribute to the health workforce by diagnosing and managing common conditions and minor surgical procedures such as VMMCs.…”
Section: Introductionmentioning
confidence: 99%